The impact of early-life antibiotics and probiotics on gut microbial ecology and infant health outcomes: a Pregnancy and Birth Cohort in Northwest China (PBCC) study protocol - Qi Qi; Liang Wang; Mitslal Abrha Gebremedhin; Shaoru Li; Xueyao Wang; Jiali Shen; Yingze Zhu; Amanuel Kidane Andegiorgish; Yue Cheng; Lu Shi; Jing Zhou; Ying Yang; et al. (BMC Pediatrics, 2022)
Abstract Background Unreasonable use of antibiotics and probiotics can alter the gut ecology, leading to antibiotic resistance and suboptimal health outcomes during early life. Our study aims are to clarify the association among antibiotic and probiotic exposure in early life, the microecology of the gut microbiota, and the development of antibiotic resistance; to investigate the long-term impact of antibiotics and probiotics on the health outcomes of infants and young children; and to provide a theoretical basis for the rational use of antibiotics and probiotics from a life course perspective. Methods The study is a prospective, longitudinal birth cohort study conducted in Shaanxi Province, China from 2018 to 2024. A total of 3,000 eligible mother–child pairs will be enrolled from rural, suburban, and urban areas. The recruitment of the participants begins at pregnancy, and the newborns will be followed up for 2 years at successive timepoints: within 3 days after birth, 42 days after birth, and at 3, 6, 12, 18, and 24 months of age. Sociodemographic data, environmental exposures, dietary patterns, psychological conditions, and medical and drug histories are collected. Cognitive and behavioural development among infants and young children and questionnaires on antibiotic knowledge and behaviour among caregivers will be collected at 12 and 24 months of age. The faecal samples are collected and analysed by 16S rRNA high-throughput sequencing and quantitative PCR (qPCR) for antibiotic resistance genes. Discussion The findings will inform antibiotic and probiotic use for pregnant women and infants and contribute to establishing rational use strategies of antibiotics and probiotics for paediatricians, health practitioners, and drug administration policy-makers. Trial registration The study was registered on the Chinese Clinical Trial Registry (ChiCTR) platform, http://www.chictr.org.cn (Record ID: ChiCTR2100047531, June 20, 2021).